Nutritional assessment of tribal women in Kainatty, Wayanad: A cross-sectional study - Sreelakshmi Mohandas; K Amritesh; Harsha Lais; Sanjeev Vasudevan; S Ajithakumari (Wolters Kluwer Medknow Publications, 2019)
Introduction: Women from a society reflect the culture that they are a part of and tribal women are the most disadvantaged considering the levels of illiteracy and ignorance. As per the National Family Health Survey 4 reports, in Kerala, undernutrition is particularly common among women from scheduled tribes, 20%. This study was done to assess the nutritional status and its associated factors among tribal women in the reproductive age group at Wayanad. Materials and Methods: A hospital-based cross-sectional study was carried out during January 2017 at Amrita Kripa Charitable Hospital in Kainatty, Wayanad. The minimum calculated sample size was 186. Using systematic random sampling, every third tribal woman in the age group of 15-49 years attending the general outpatient department as patient or bystander was interviewed using a pretested semi-structured questionnaire and examined for height, weight, body mass index, and pallor. Data were analyzed using SPSS version 21. Results: Data were collected from a total of 223 study participants; 53.8% of them were undernourished (< 18.5 kg/m2) with 25% severe underweight and 3.1% and 2.7% preobese and obese women. Participants who were <30 years of age (0.001), those who used smokeless tobacco (0.008), and women from the Paniya tribe 0.001 had significantly higher odds of undernutrition. Conclusion: Almost one-fourth of the study participants were severely undernourished and 5.8% belonged to obese and preobese categories, thereby indicating the gravity of the nutritional difficulties among tribal women. A well-planned and coordinated effort is needed to address the scenario of malnutrition among tribal women.